Synthesis, characterization, and computational modeling of 6, 6'-(((2-hydroxyethyl)azanediyl)bis(methylene))bis(2, 4-di-tert-butylphenol) modified group 4 metal alkoxides. Issue 9 (2nd May 2020) - Boyle, Timothy J.; Rimsza, Jessica M.; Farrell, Joshua; Robinson, Xavier J.; Guerrero, Fernando; Cramer, Roger; Perales, Diana; Renehan, Peter
Abstract: The coordination behavior of the tridentate alkoxy ligand 6, 6'-(((2-hydroxyethyl)azanediyl)bis(methylene)) bis(2, 4-di- tert -butylphenol) (termed H3 -AM-DBP2 ) with group 4 metal alkoxides ([M(OR)4 ]) in a 1:1 ratio was previously found to generate [(ONep)Ti( κ 4 ( O, O', O", N )-AM-DBP2 )] and [(OR)Zr( κ 4 (μ -O, O', O", N )-AM-DBP2 )]2 (M = Zr, Hf). Additional studies revealed that increasing the stoichiometric ratio to 1:2 H3 -AM-DBP2 :[M(OR)4 ] led to the isolation of [(ONep)Ti( κ 4 (μ -O, O', O", N )-AM-DBP2 )(μ-ONep)Ti(ONep)3 ] (1 )tol, [(OBu t)Zr( κ 4 (μ- O, O', O", N )-AM-DBP2 )(μ-OBu t )Zr(OBu t )3 ] (2 ) and [(OBu t )Hf( κ 4 (μ- O, O', O", N )-AM-DBP2 )(μ-OBu t)Hf(OBu t )3 ] (3 ). The asymmetric dinuclear complexes of 1 -3 resemble the chelation of a [M(OR)4 ] moiety to a "(OR)M( κ 4 ( O, O', O", N )-AM-DBP2 )" fragment. The metal complexed by the AM-DBP2 ligand has a pseudo octahedral geometry while the other metal adopts an intermediate trigonal bipyramidal (TBP-5)/square base pyramidal ( SBP-5 ) geometry for 1 but a distorted SBP -5 for both 2 and 3 . The structure and properties of 1 -3 were analyzed by computational modeling and fully characterized by standard analytical methods. Graphical Abstract: